Measuring consumer perceptions of online shopping convenience - Ferreira, Margarida Bernardo (2017)
The aim of this master thesis is to identify which dimensions of convenience affect consumers’ intention of using online shopping. Also it explores a conceptual model to measuring consumer perceptions of online shopping convenience. This paper contains prospects about online consumer behavior, and the results have important implications for retailers, managers and marketers, related to online shopping strategies. An empirical investigation was carried out to test the hypotheses. In order to answer the research question, data collection was done through a web-based survey with a convenient sample as a means to collect customers’ feedback, opinion, feelings, attitudes, and perceptions about their last online shopping experience. The findings were further discussed in the light of existing literature. The sample includes 250 young Portuguese anonymous participants. It was used a Confirmatory Factor Analysis (CFA) in the scale validation for the analysis and measurement of specific constructs and a Structural Equation Model (SEM) in order to test the relationships of the model. The results reveal that the model proposed Possession, Transaction and Evaluation are the dimensions with more influence in online shopping convenience. The outcomes of this study help to understand which dimensions of online convenience prevent or encourage the use intention of online shopping. The results not only help develop a better understanding of online shopping theories for researchers, but they also offer viable knowledge to those involved in promoting online shopping to potential purchasers.